MUNCHAUSEN SYNDROME BY PROXY - A REAL PEDIATRIC PROBLEM? - Daniela Pacurar; Maria Runcan; Anca Popescu; Gabriela Lesanu; Dumitru Oraseanu (Amaltea Medical Publishing House, 2015)
Munchausen syndrome and Munchausen by proxy syndrome belong belong to a group of disease called "factitious disorder" and are severe mental disorders having the "end" position for a healthy person to become patient, respectevely to "create" a disease to another person, asking or requiring medical intervention for him/her. Munchausen syndrome by proxy is rare, but it is diffi cult to be recognized and confi rmed, is a form of abuse, particularly against children, potentially lethal, often misunderstood. Many methods are used by adults counterfeiters to induce a false child's condition: poisoning, injury, producing bleeding, infection. Complaints exposed by the mothers as belonging to the child are not for a personal benefi t, but are justifi ed by a desire to be a "hero" mothers and to play the role of the people most attached and thoughtful of their child. Diagnosis should include evaluation of the child, parents and family and is based on suggestive elements: child with multiple health problems that do not respond to treatment or recur under proper therapy, laboratory investigations discrepancies, child's signs and symptoms disappear in the absence of the parent. The false disease of the child, intentionally distorted described by adult, do not realy affect him/her, but the diagnostic process and medical treatment can cause pain and discomfort. Ethical and legal issues associated with MSBP involves healthcare professionals by the medical consequences on the child as a result of false complains described by the parent. Education of patient, family and medical personnel is a very important step in the recognition, prevention and treatment of MSBP.